Cover Picture: Dinuclear Face‐Sharing Bi‐octahedral Tungsten(VI) Core and Unusual Thermal Behavior in Complex Th Tungstates (Chem. Eur. J. 21/2015). Issue 21 (18th May 2015) - Xiao, Bin; Gesing, Thorsten M.; Robben, Lars; Bosbach, Dirk; Alekseev, Evgeny V.
<x xml:space="preserve">Abstract</x> A rare case of a confacial bi‐octahedral tungsten(VI) core was isolated from a thorium tungstate system. These compounds are constructed from a complex polyoxometalate‐like cage and exhibit unexpected thermal behavior. Interestingly, the cage with a threefold rotation axis passing through its center has a cross‐section remarkably similar to a six‐leafed lily. A comprehensive discussion can be found in the Full Paper by E. V. Alekseev et al. on page 7746 ff.